2022
DOI: 10.3390/nu14030453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein and Processing on Gut Microbiota—A Systematic Review

Abstract: The effect of diet on the composition of gut microbiota and the consequent impact on disease risk have been of expanding interest. The present review focuses on current insights of changes associated with dietary protein-induced gut microbial populations and examines their potential roles in the metabolism, health, and disease of animals. Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol was used, and 29 highly relevant articles were obtained, which included 6 mouse studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 146 publications
(214 reference statements)
3
57
0
1
Order By: Relevance
“…Most dietary nutrients are fully digested and absorbed at the end of the ileum, whereas undigested complex fragments are fermented in the hindgut ( Zhang et al, 2018b ). During this process, microbes promote nutrient application, and the protein sources can shape the composition of intestinal microbiota ( Wu et al, 2022 ). The Proteobacteria phylum, as facultative anaerobes, cannot consume fiber, but can interfere with host nutrition by metabolizing fermentation products to carbon dioxide in the presence of oxygen ( Litvak et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most dietary nutrients are fully digested and absorbed at the end of the ileum, whereas undigested complex fragments are fermented in the hindgut ( Zhang et al, 2018b ). During this process, microbes promote nutrient application, and the protein sources can shape the composition of intestinal microbiota ( Wu et al, 2022 ). The Proteobacteria phylum, as facultative anaerobes, cannot consume fiber, but can interfere with host nutrition by metabolizing fermentation products to carbon dioxide in the presence of oxygen ( Litvak et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that high levels of circulating adiponectin can protect against weight gain [ 35 ]. Wu S et al stated that the quality of protein and optimal food processing conditions are important, and have a positive effect on gut microbiota and dysbiosis [ 36 ]. Our study reported increased adiponectin levels in Group A, which was supported by Kondo et al [ 37 ] and Bluher et al [ 38 ], but the opposite was reported by Nassis et al [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, interventions to increase fresh food selection and purchases in tribal stores have shown promise and should be more widely implemented in other tribal communities [103,105,106]. Beyond a variety of fruits and vegetables, interventions targeting GM health could feature "microbe-friendly" foods, such as fermented and high fiber foods [8,107] and plant protein [84]. The recent addition of fresh food within some dollar stores [108] represents another promising development that should be evaluated, especially in rural tribal communities.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis focuses on the availability and variety of foods that promote GM health: fresh or frozen fruits and vegetables, whole grain bread, dairy, and unprocessed meat [82][83][84][85][86]. We also report findings on alcohol and tobacco availability, products known to contribute to GM dysbiosis [7,87] and utilized at high rates in some tribal communities [71,[76][77][78].…”
Section: Methodsmentioning
confidence: 99%